Evaluasi Usability Desain Website Perpustakaan Menggunakan Kuesioner Nielsen Attributtes Of Usability Di Universitas Medan Area - Ramadhan, Fahmi; Sutrisno, Sutrisno; Hasibuan, Chalis Fajri (Universitas Medan Area, 2024)
Technological advancements in the globalization era have significantly influenced various sectors, including education. The University of Medan Area (UMA) library leverages technology to provide academic information services through its website. This study evaluates the usability of UMA's library website using Nielsen's Attributes of Usability (NAU), which include learnability, efficiency, memorability, errors, and satisfaction. Data were collected through questionnaires and analyzed using validity, reliability tests, and non-parametric statistical methods. The results show a significant correlation between usability dimensions and user satisfaction. Learnability, efficiency, errors, and satisfaction exhibit strong correlations, while memorability demonstrates a moderate correlation. Recommendations focus on improving navigation, organizing content structure, enhancing mobile responsiveness, and integrating social media. These efforts aim to improve accessibility, user engagement, and comfort. The study provides essential insights for developing UMA's library website into a more user-friendly platform that effectively supports students’ and lecturers’ academic success.